HUBUNGAN POLA ASUH ORANG TUA DALAM PEMBERIAN MAKAN DENGAN KEJADIAN STUNTING PADA ANAK USIA 2-5 TAHUN DI PUSKESMAS PORIS GAGA LAMA KOTA TANGERANG - sultan fatahillah sultan (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Stunting is a chronic nutritional problem characterized by a child's height being below the age standard due to long-term malnutrition. Parenting practices in feeding are suspected to have a significant influence on the incidence of stunting. To determine the relationship between parental feeding practices and the incidence of stunting in children aged 2-5 years at the Poris Gaga Lama Community Health Center, Tangerang City. This study used a quantitative method with a correlational analysis approach and a cross-sectional design. Sampling was conducted using purposive sampling, with a total of 74 respondents. 82.4% of respondents implemented appropriate feeding practices, while 17.6% did not. The distribution of stunting showed that 82.4% of children were normal, 13.5% were stunted, and 4.1% were severely stunted. The Spearman rank test indicated a significant relationship between feeding practices and the incidence of stunting (coefficient value = 0.997; p-value < 0.001). Keywords: Parenting, feeding practices, stunting